A review of Artificial Intelligence (AI) As a tool for creative expression - Mohd Radzuan, Lili Eliana; Abdul Razak, Mohamed Razeef; Ahmad Fauzi, Farrah Hanani (Journal of Islamic, Social, Economics and Development, 2025)
Artificial Intelligence (AI) has made a profound impact across various fields, with art and design standing out as areas experiencing notable transformation. This review delves into the role of AI as a powerful tool for creative expression, particularly focusing on its effects on artistic creation and design workflows. By analyzing recent advancements in AI technologies and their applications within art and design, this article highlights how AI is augmenting, reshaping, and even challenging traditional creative practices. From assisting artists with ideation to generating entirely new forms of artwork, AI is opening doors to innovative possibilities. This review synthesizes current research findings, identifies key trends, and discusses AI’s potential to influence the creative industries’ future. Additionally, it considers the ethical and intellectual property challenges that arise, emphasizing the complex relationship between technology and human creativity in a rapidly evolving landscape.